Perhitungan Biaya Produksi dalam Sistem Pesanan Kain Batik Abstrak IKM Batik Rasya - Nureni Wildayani; Faturahman Faturahman; Puteri Anggi Lubis (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was conducted at IKM Batik Rasya. The aim of this research is to find out how to calculate the production costs of abstract batik cloth at IKM Batik Rasya and to find out how to calculate the production costs of abstract batik cloth in accordance with the order system. This research uses descriptive research with a qualitative approach. The analysis carried out is calculating the current cost of production by determining the Job Order Costing method, then comparing the calculation rate for the cost of production with the previous method. This research data was obtained from observations, interviews and documentation with the owner of IKM Batik Rasya. The results of the research show that from calculations using the Job Order Costing method, when compared with the rates set by the IKM Batik Rasya, calculations using the Job Order Costing method provide calculation results for the basic production cost of job order costing of IDR 38,976,000.00 with a price per unit of IDR 194.880,00, while the total calculation for the IKM Batik Rasya cost of production is IDR 35.422.000,00 with a price per unit of IDR 177.110,00, so the difference in calculation between the two is IDR 3,554,000.00